The relation between central variables, electromyography signals and peripheral microcirculation during intensive treadmill exercise. (July 2019) - Ratnovsky, Anat; Yanovich, Ran; Kesner, Dikla; Ketko, Itay; Schermann, Haggai; Heled, Yuval; Ovadia-Blechman, Zehava
Abstract: Background: Aerobic exercise under muscle fatigue can lead to muscular damage and injuries. Finding the correlations between central and peripheral microcirculation variables, as well as with electromyography signals of leg muscles during aerobic exercise, may contribute to early muscle fatigue identification. The goal of this study was to characterize the peripheral compensation following intensive exercise for assessment of muscle performance based on non-invasive techniques. Methods: The experimental protocol included two days of measurements. Electrocardiography tests and anthropometric measurements of the volunteers (N = 14) were carried out. The maximal aerobic ability (first day), as well as electromyography and cutaneous hemodynamic variables (second day) were measured during treadmill run. A score-based Bayesian network machine-learning algorithm was used to predict ventilation values based on cutaneous hemodynamic measurements. Findings: Transcutaneous oxygen tension can be used to identify anaerobic threshold for both trained and untrained subjects during treadmill running, while electromyography can be used to identify anaerobic threshold only of trained subjects. Predicted values of ventilation, based on the transcutaneous oxygen tension, showed high correlation with actual values. Prediction accuracy was better among trained subjects, compared to the untrained ones. Interpretation: Transcutaneous oxygen tension could be used for prediction of maximal oxygen consumption during intense exercise and thus may provide improved assessment of premature fatigue during exercise. Highlights: Cutaneous variables could reflect local compensation mechanisms due to exercise. Electromyography and cutaneous oxygenation can identify the anaerobic threshold. A coupling between the peripheral and the central systems was observed. Cutaneous oxygenation may predict minute ventilation during intensive exercise. The results may have an impact on muscle performance assessment during exercise.